Linguistic Means of Bessarbian Life Reflection in Virtual Media Space - Chetverikova, Olena (Journal of Danubian Studies and Research, 2023)
Today in Southern Bessarabia, as well as around the world, the development of information and communication technologies is rapidly gaining momentum. We feel the influence of bloggers, opinion leaders, and active community representatives on the general public opinion. Virtual media are an effective platform for covering important society issues and achievements of the region, town, village, or district that are interesting and effective due to modern realities. There is definite transition from traditional ways of communication to new and progressive ones, which replace the usual communicative practices. This can be attributed to certain reasons, such as the growing popularity of virtual media among different age groups and, consequently, the emergence of new concepts and realities that require specific language units to nominate them. As a universal means of communication and information exchange, the Internet is a reflection of linguistic reality and the changing lingual and cultural environment. At the same time, there is a process of enriching the lexical and semantic structure of languages, including borrowings, numerous neologisms and newborn abbreviations. Various genres of virtual media communication are realized in new textual and discursive practices. The trend of democracy and simplification is reflected in all areas of speech, which are manifested in online texts that leads to changes in official language standards of communication and attracts the attention of many scholars. The desire to deepen the informativeness of the statement naturally acts as a catalyst for constant changes in media language that is why such research problems need comprehensive study.